Exponential stability of an upwind difference scheme for a quasilinear hyperbolic system with nonlinear boundary conditions: Exponential stability of an upwind difference scheme for a quasilinear hyperbolic system with nonlinear boundary conditions - Aloev, R. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation. In this paper, we numerically study the stability of a difference scheme for a mixed problem for a quasilinear hyperbolic system of equations. A difference scheme was constructed, and a theorem on the stability of the numerical solution was proved.